Abnormalities in Haemoglobin Synthesis: Thalassemia and Itâs Epidemiology - Wulandari, Retno Dwi (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2016)
Hemoglobinopathy includes structural abnormalities and haemoglobin synthesis disorders (thalassemia), is a single gene disorder that was originally found in malaria endemic areas but nowadays can be found all over the world. The birth rate of homozygous or compound heterozygous hemoglobinopathies, including alpha and beta thalassemia is less than 2.4 per 1000 births. Sickle cell anemia is the most prevalent compared to beta major and HbE-beta thalassemia. In Southeast Asia with more than 600 million people, abnormalities in hemoglobin including thalassaemia, HbE and HbCS are the most common and highly prevalent genetic disorders. Indonesia, has several areas that are endemic to malaria, there are many cases of abnormalities in Hb including thalassemia. If the percentage of carriers is associated with the birth rate and the number of Indonesian population and based on the study, it is estimated that the number of thalassemia patients born each year around 2500 children. As the case of thalassemia is increasing from year to year, it is necessary that prevention starts with screening in individuals who have relatives known as a carrier or thalassemia patient.Â